Dobbelary: Om van baie verloorders te maak en van min wenners? - D. P. Veldsman (Verbum et Ecclesia, 1993)
Gambling: Making losers of many and winners of few? The question of the desirability of legalising gambling in South Africa and the affirmative proposal by the Howard Commission Report (March 1993) to this extent, is critically addressed in this short paper. Gambling, being a game of chance - and certainly already a well established and favourite pastime in South Africa - invites an understanding of the element of chance.